ESSENTIALS OF SOCIAL MEDICINE AND MEDICAL ETHICS: A BOOK REVIEW - Dencheva, Maria (Sanamed, 2024)
BOOK DETAILS First Book: Essentials of Social Medicine and Medical Ethics © First Edition, 2016 Editor: Lydia Katrova Publisher: Lydia Katrova-Leading Technologies in Dentistry, Sofia, Bulgaria ISBN Number: 978-954-90363-5-0 Second Book: Essentials of Public Health and Healthcare Management © Second Edition, 2017 Editor: Lydia Katrova Publisher: Lydia Katrova-Leading Technologies in Dentistry, Sofia, Bulgaria ISBN Number: 978-954-90363-7-4 Third Book: Essentials of Dental Health and Dental Practice Management © Second Edition, 2017 Editor: Lydia Katrova Publisher: Lydia Katrova-Leading Technologies in Dentistry, Sofia, Bulgaria ISBN Number: 978-954-90363-4-3 ABOUT THE BOOKS This review of the trilogy written by Prof. Lydia Katrova illustrates the essential role of dentists’ professionalization within the harmonized European Union framework of dental curriculum competences. As one of the founders of the Department of Dental Public Health at the Faculty of Dental Medicine of the Medical University of Sofia, the author leverages her experience as a practicing dentist, researcher, and educator to provide the program with appropriate instructional tools. The series of three books cover the disciplines of Social Medicine, Medical Ethics, Healthcare Management, and Dental Practice Management. The work reflects the dynamics of radical reforms in healthcare at national, European, and global levels, as well as the evolution of the dental profession within the context of Bulgaria’s European integration and the challenges of the globalizing dental care market. The selection of material included in these books and their structure align with the course program agreed upon by the Department of Public Dental Health, aiming to fulfill the overall curriculum objectives for the educational degree of "Doctor of Dental Medicine" in accordance with European and global trends in dental education. The textbooks are organized to succinctly present the most important elements of socio-professional identification and professional achievements of dentists, thereby equipping graduating dentists in Bulgaria (and beyond) to successfully establish independent dental practices in any European country. The first book of the series, entitled “Essentials of Social Medicine and Medical Ethics," is divided into two parts, each comprising four and three chapters respectively. Part 1 (chapters 1 through 4), focused on Social Medicine, employs an interdisciplinary approach to enhance the individual professional development of dentists through the following key competences: -Understanding social and public health phenomena and processes occurring at the individual, group, and community levels. -Analyzing health status determinants and relevant health indicators for public health. -Making decisions based on critical evaluation of facts and circumstances. -Addressing technological, medical, legal, and ethical concerns that arise during professional activities (1). Part 2 of the first book, dedicated to Ethics, consists of three chapters presenting the ethical framework for professional dentists, governing their relationships with patients, colleagues, and society in accordance with shared values in the social environment and a common understanding of morality. The second book, titled "Essentials of Public Health and Healthcare Management," comprises nine chapters and aims to equip readers with knowledge, professional skills, and motivation in various areas, including: -Understanding the development of healthcare within the broader societal context. -Implementing effective management strategies within the health system. -Preparing Doctor of Dental Medicine professionals to function effectively within a regulated profession. -Managing dental practices within real social and market environments. -Engaging in partnerships for the implementation of community measures aimed at achieving individual and public oral health goals. I concur with the sentiments expressed by Prof. Nairn Wilson in the Foreword of this book: "...Professor Katrova is to be congratulated in bringing together a wealth of information in a succinct, carefully crafted text. As such, this book is an important source of reference for dentists in Bulgaria and beyond seeking knowledge and understanding of public health and healthcare management. Dentists with this knowledge and understanding will, hopefully play an important role in ensuring that the importance of dentistry and oral health is not overlooked in the further development of existing healthcare systems”. Nairn H F Wilson CBE DSc (h.c.) PhD MSc BDS FDS Edin & Eng FFD FFGDP FCDSHK DRD FHEA FACD FADM FKC. Professor of Dentistry, King‘s College London, London” (2). The third book, titled "Essentials of Dental Health and Dental Practice Management," aims to assist dental students and practitioners in finding their optimal practice patterns and establishing suitable working environments to achieve professional prosperity while maintaining their health and longevity. Additionally, it aims to sensitize them to the population’s needs for appropriate services, prevention, and improved quality of life. The textbook comprises three parts: -The first part, including chapters 1 through 4, addresses the assessment of dental health, the promotion of a healthy environment and behaviors, and the prevention of dental diseases. -Part two, comprising chapters 5 through 9, delves into the principles of ergonomics, organizing the workplace, conducting procedures, timing, and recommendations for teamwork. -Part three, featuring chapters 10 and 11, focuses on establishing and managing dental practices (3). Upon reading the words of appreciation on page 5 of the book, it becomes evident that this robust work is the result of a long and successful collaboration with world-renowned specialists and institutions in the fields of public health and dental education, including: The Association for Dental Education in Europe (ADEE), The Council of the Chiefs Dental Officers in Europe (CECDO), The School of Public Health at Harvard University (SPH HU), The University "René Descartes," Laboratoire d’Ethique Medicale, Paris and MEDIS Institute, Munich, Germany While there are numerous publications containing statistical information, health strategies, and investigations into various aspects of public health, there are few focused specifically on the needs of dental school graduates to become competent in the framework issues (political, social, epidemiological, professional, legislative) necessary to succeed as independent dental practitioners. The content and structure of this work align with the general educational objectives of the undergraduate dental curriculum harmonized with EU competences. The particular advantages of these books compared to competing publications lie in their focused, balanced, and concise structure, allowing for adaptation and customization to national particularities while retaining appropriate global and enduring professional concepts. This work presents an original concept and references the newest facts and findings relevant to the dental profession. It represents a genuine effort to "translate" complex social and professional issues into terms understandable and implementable by dental practitioners in their work, motivating them to collaborate in the realization of health strategies while preserving their professional autonomy and integrity. These books serve as suitable tools for this purpose and are unlikely to become outdated, as the pursuit of professionalism never does.